Studi Evaluatif Relevansi Model Pengembangan Kurikulum PGSD dengan Kurikulum SD di Bandar Lampung - Deviyanti Pangestu; Tegar Pambudhi; Maman Surahman (Universitas Lampung, 2019)
The purpose of this study (1) to find out the relevance of the curriculum model development of Elementary School Teacher Education with the Elementary School curriculum, (2) to produce a level of improvement in courses that have relevance to the Elementary School curriculum, 3) produce textbooks. The method used in this study is Research and Development. Data collection used questionnaire and structured interview. The results showed that the average score of pedagogical competence of elementary school teachers was included in the excellent category. average score of professionalism of teachers included in the excellent category. The pedagogical abilities and professional abilities of teachers in relation to the relevance of the Elementary School Teacher Education curriculum with the curriculum in Primary Schools are included in the excellent category.Keywords: subject curriculum, integrated curriculum, research and developmentDOI: http://dx.doi.org/10.23960/jiip.v1i2.18027